The Impact of a Video Game on Criminal Thinking: Implicit and Explicit Measures. (December 2014) - Shaw, Julia; Crosby, Kimberly; Porter, Stephen
Background: Debate regarding the potential repercussions of engaging with videogames that promote violence and crime has been part of public discourse for decades. The present study seeks to add to the debate by investigating some of theunexplored links betweenpro-criminal videogames andantisocial cognitive processes . Aim: This study examined whethercriminal thinking could bemanipulated by exposure to common criminal stimuli: a popular North Americannews show and a popular antisocialvideogame (GRAND THEFT AUTO IV). Method: Participants ( N = 136) were assigned to one offour conditions (criminal news, non-criminal news, criminal gameplay, noncriminal gameplay) followed byimplicit (Implicit Association Test) andexplicit (questionnaires)measures of criminal thinking. Results: Results indicated that engaging in criminal video gameplay had animmediate effect on implicit measures of criminal thinking, but not on explicit measures of criminal thinking. Implications: This study builds on the present literature by examiningsources of criminal thinking and theusefulness of virtual crime methodologies andimplicit measures for experimental paradigms in this field.